Jorge Fernández - Ring Oscillator PUF on FPGA: Design and Characterisation by Using Second-Order Compensated Measurement - Fernández, Jorge (Jornada de Jóvenes Investigadores del I3A, 2022)
Ring Oscillator PUF on FPGA: Design and Characterisation by Using Second-Order Compensated Measurement